Highlights in practical applications of agents, multi-agent systems, and trust-worthiness : The PAAMS Collection : International Workshops of PAAMS 2020, L'Aquila, Italy, October 7-9, 2020, Proceedings /: The PAAMS Collection : International Workshops of PAAMS 2020, L'Aquila, Italy, October 7-9, 2020, Proceedings. (2020) - Unknown
No abstract available